2018
DOI: 10.1016/j.ibror.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The monoaminergic pathways and inhibition of monoamine transporters interfere with the antidepressive-like behavior of ketamine

Abstract: Ketamine (KET), a NMDA receptor antagonist, has been studied for its rapid and efficacious antidepressant effect, even for the treatment-resistant depression. Although depression is a major cause of disability worldwide, the treatment can be feasible, affordable and cost-effective, decreasing the population health burden. We evaluated the antidepressive-like effects of KET and its actions on monoamine contents (DA and its metabolites, as well as 5-HT) and on tyrosine hydroxylase (TH). In addition DAT and SERT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
1
2
0
1
Order By: Relevance
“…A neural mechanism involved in the antidepressant effects of KET is the AMPA receptor stimulation, which has been shown to mediate an increase in the brain extracellular levels of serotonin, as also shown by our group ( 7 ). However, mechanisms other than NMDA receptor inhibition play a key role in the antidepressant effect of KET, suggesting that the KET antidepressant effect goes beyond the NMDA receptor inhibition and AMPA receptor activation.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…A neural mechanism involved in the antidepressant effects of KET is the AMPA receptor stimulation, which has been shown to mediate an increase in the brain extracellular levels of serotonin, as also shown by our group ( 7 ). However, mechanisms other than NMDA receptor inhibition play a key role in the antidepressant effect of KET, suggesting that the KET antidepressant effect goes beyond the NMDA receptor inhibition and AMPA receptor activation.…”
Section: Introductionsupporting
confidence: 69%
“…This synergistic effect was probably the result of inhibitions of GSK-3 and HDAC, important targets for both drugs. Recently, we also demonstrated that the fast antidepressant effects of KET are, at least partly, due to its action on striatal monoaminergic pathways ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been shown that an increase in dopamine levels accompanies the use of several antidepressants. For instance, Viana et al demonstrated that ketamine administration caused a decrease in immobility time and an increase in dopamine concentration in the striatum of mice . In some models of depression, a decrease in dopamine and norepinephrine in the striatum is observed .…”
Section: Resultsmentioning
confidence: 99%
“…Em relação ao sistema serotoninérgico, estudos mostraram que fármacos, como a fluoxetina, imipramina e cetamina aumentam a fosforilação de proteínas responsáveis pela modulação dos receptores serotoninérgicos (GRIECO et al, 2017;VIANA et al, 2018). Grieco et al (2017) ARONSTAM, 1990;ZHAO;SUN, 2008;YAMAMOTO et al, 2013).…”
Section: Discussionunclassified